Ecophysiology of indigenous trees in agroforestry systems in the semi-arid tropics - Broadhead, Jeremy (2000)
Increasing demand for timber, fuelwood and other forest products has outstripped production in many areas of the semi-arid tropics, leading to deforestation and land degradation resulting from erosion and nutrient depletion. Agroforestry offers the potential to provide forest products, improve productivity and reduce soil erosion and environmental degradation. However, as previous reports have shown that competition between trees and crops for water in semi-arid areas adversely affects crop yields, attention has turned towards studies of the existing practice of boundary planting, where low tree planting densities and the associated benefits of land demarcation and soil stabilisation increase the viability of incorporating trees into crop land. The aim is to select and manage tree species in ways that limit their negative effect on crop yields and improve the overall value of the system.